This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: hernandez (ah29758) – M408D Quest Homework 1 – pascaleff – (54550) 1 This printout should have 14 questions. Multiplechoice questions may continue on the next column or page – find all choices before answering. 001 10.0 points Determine if the limit lim x → 1 x 8 − 1 x 7 − 1 exists, and if it does, find its value. 1. limit = −∞ 2. limit = ∞ 3. limit = 8 7 correct 4. none of the other answers 5. limit = 7 8 Explanation: Set f ( x ) = x 8 − 1 , g ( x ) = x 7 − 1 . Then lim x → 1 f ( x ) = 0 , lim x → 1 g ( x ) = 0 , so L’Hospital’s rule applies. Thus lim x → 1 f ( x ) g ( x ) = lim x → 1 f ′ ( x ) g ′ ( x ) . But f ′ ( x ) = 8 x 7 , g ′ ( x ) = 7 x 6 . Consequently, limit = 8 7 . 002 10.0 points Determine if the limit lim x →−∞ (1 − 5 x ) 1 6 x exists, and if it does, find its value. 1. none of the other answers 2. limit = 1 correct 3. limit = −∞ 4. limit = 0 5. limit = e 1 5 6. limit = e − 5 7. limit = ∞ Explanation: Since the limit has the form lim x →−∞ (1 − 5 x ) 1 6 x = ∞ , we first take logs and evaluate lim x →−∞ ln braceleftBig (1 − 5 x ) 1 6 x bracerightBig . But ln braceleftBig (1 − 5 x ) 1 6 x bracerightBig = ln(1 − 5 x ) 6 x . By L’Hospital’s Rule, therefore, lim x →−∞ ln braceleftBig (1 − 5 x ) 1 6 x bracerightBig = lim x →−∞ − 5 6 parenleftBig 1 1 − 5 x parenrightBig = 0 . Consequently, the limit exists and limit = e = 1 . 003 10.0 points Determine if the improper integral I = integraldisplay ∞ 6 2 ( x + 4) 2 dx converges, and if it does, compute its value. hernandez (ah29758) – M408D Quest Homework 1 – pascaleff – (54550) 2 1. I = 3 7 2. I = 1 5 correct 3. I = − 1 5 4. I doesn’t converge 5. I = 2 11 Explanation: The integral is improper because of the infi nite interval of integration. To overcome this we set I = lim t →∞ integraldisplay t 6 2 ( x + 4) 2 dx whenever the limit on the right hand side exists. Now integraldisplay t 6 2 ( x + 4) 2 dx = bracketleftBig − 2 x + 4 bracketrightBig t 6 = − 2 t + 4 + 1 5 ....
View
Full
Document
This note was uploaded on 11/15/2011 for the course M 408 D taught by Professor Textbookanswers during the Spring '07 term at University of Texas at Austin.
 Spring '07
 TextbookAnswers

Click to edit the document details